A description of the guidelines for family members on how to cope and support a person with a head injury - Iyambo, Maria Tegelela; Small, Louis; Van Dyk, Agnes; Kamenye, Esther (International Journal of Health, 2017)
The purpose of this article is to describe the guidelines for the family members on how to cope and support a person with a head injury. A qualitative explorative, descriptive and contextual research design was conducted utilizing individual in-depth face-to-face interview to gather data from family members of a person with a head injury. This study was conducted in three of the northern regions of Namibia, i.e. Oshana, Omusati and Ohangwena. Data was analyzed using Tech’s method for content analysis.The results of this study showed that family members of a person with head a injury had varied and different experiences varying from different feelings, challenges and support to them.Based on these findings, the guidelines were developed to assist the family members of a person with a head injury on how to cope and support the person with a head injury. These guidelines may be implemented by any family who are taking care of a person with a head injury.